THREE MODELS OF US FOREIGN AID POLICY: A COMPARATIVE TEST - Afrimadona, Afrimadona , (Jurnal Mandala, 2018)
This article aims to test competing explanations about the US foreign aid policy, namely interest-driven theory, humanitarian theory, and domestic political theory. Using longitudinal data on the amount of Official Development Assistance provided by the US to 155 recipient countries from 1960 to 2008, analyzed using random coefficient models, the research found that humanitarian and domestic political theories can account for the US foreign aid policy to the recipient countries for almost five decades better than the interest-driven theory. Generally, the US were more likely to send aid to poorer countries and/or countries where the US-based NGOs were actively involved. The econometric models also show that there are some cross-sectional and temporal variations in the aid. On average, countries receiving high amount of aid in the 1960s tend to have lower annual growth rate in the money they received from the US.